Hidden aspects of pre-service geography teacher education in Slovenia. Vision versus reality - Tatjana RESNIK PLANINC (European Journal of Geography)
Educators of future teachers are constantly faced with the changing demands of modern times in providing quality school education. The process of educating preservice teachers involves many hidden aspects that even educators of pre-service teachers themselves are often unaware of, as they are subtly hidden behind likeable professional eloquence. For decades, the pre-service geography teacher education in Slovenia has been driven by the educators’ profound belief in the significance of preparing students for their future professions, regardless of the, often hidden, obstacles that they have had to overcome. Through a qualitative pilot study among former students on the geography teacher education study programme in Slovenia, we aimed to identify strengths and weaknesses of the existing programme and suggest possible changes that could lead to its improvement